Characterization of the petiole length in soybean compact architecture mutant M657 and the breeding of new lines - Hua-wei GAO; Ru-jian SUN; Meng-yuan YANG; Long YAN; Xian-zhong HU; Guang-hui FU; Hui-long HONG; Bing-fu GUO; Xiang ZHANG; Li-ke LIU; Shu-zhen ZHANG; Li-juan QIU (Journal of Integrative Agriculture, 2022)
Phenotypic screening of soybean germplasm suitable for high planting density is currently the most viable strategy to increase yield. Previous studies have shown that soybean varieties with dwarf features and a short petiole often exhibit a compact plant architecture which could improve yield through increased planting density, although previously reported short petiole accessions were ultimately not usable for breeding in practice. Here, we established a method to assess petiole length and identified an elite mutant line, M657, that exhibits high photosynthetic efficiency. The agronomic traits of M657 were evaluated under field conditions, and appeared to be stable for short petiole across seven locations in northern, Huang–Huai, and southern China from 2017 to 2018. Compared with the Jihuang 13 wild type, the mutant M657 was shorter in both petiole length and plant height, exhibited lower total area of leaf, seed weight per plant and 100-seed weight, but had an increased number of effective branches and the growth period was prolonged by 2–7 days. Using M657 as a parental line for crosses with four other elite lines, we obtained four lines with desirable plant architecture and yield traits, thus demonstrating the feasibility of adopting M657 in breeding programs for soybean cultivars of high density and high yield.